2022
DOI: 10.1136/bmjopen-2021-058464
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent vision and hearing impairment associated with cognitive dysfunction in a population aged 85+ years: the Ural Very Old Study

Abstract: ObjectiveTo assess the prevalence of vision impairment, hearing impairment and dual sensory impairment (DSI) as combination of vision and hearing impairment, in association with cognitive dysfunction in a population aged 85+ years.MethodsThe cross-sectional population-based Ural Very Old Study, conducted in rural and urban Bashkortostan, Russia, between 2017 and 2020, included a detailed ocular and systemic examination with assessment of moderate to severe vision impairment (MSVI)/blindness (best-corrected vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…RNA sequencing analysis has revealed that ARHL shares a common causative gene with Alzheimer’s disease (AD; Xue et al, 2021 ). Numerous experimental studies have identified multiple mechanisms by which SNHL can lead to CI ( Loughrey et al, 2018 ; Choi et al, 2021 ; Bikbov et al, 2022 ). In response to these findings, researchers have proposed three hypotheses on how SNHL brings about CI: the cognitive load (CL) hypothesis, the co-morbidity hypothesis, and the sensory deprivation hypothesis ( Slade et al, 2020 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing analysis has revealed that ARHL shares a common causative gene with Alzheimer’s disease (AD; Xue et al, 2021 ). Numerous experimental studies have identified multiple mechanisms by which SNHL can lead to CI ( Loughrey et al, 2018 ; Choi et al, 2021 ; Bikbov et al, 2022 ). In response to these findings, researchers have proposed three hypotheses on how SNHL brings about CI: the cognitive load (CL) hypothesis, the co-morbidity hypothesis, and the sensory deprivation hypothesis ( Slade et al, 2020 ; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory function decline is also caused by aging, in which vision and hearing especially affect the daily life of the elderly. Studies 13–15 have shown that visual and hearing difficulties in seniors can negatively influence their cognitive function. The elderly with visual difficulty would have problems with seeing objects, which further affects their perception and understanding of the surrounding environment 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, visual and hearing difficulties of the elderly may affect their mental health, leading to problems such as loneliness and depression, which further affect their cognitive function. It has been examined that difficulty in dual sensory (vision and hearing) has greater negative effects on their cognitive function 13–15,17 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations